Minat Pengunjung Di Pasar Tradisional Sukorejo Kec. Sukorejo Blitar - Sabrina Amalia; Cici Widiana Wijayanti; Azizaturrohmah Azizaturrohmah; M.Niam Roziqul Akbar; Nanda Aulia Minka; Isna Khuni Mualimah (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Traditional markets are places of interaction between sellers and buyers which are characterized by direct transactions and frequent bargaining processes. The existence of traditional markets makes people happy because traditional markets provide many basic daily needs and necessities and of course the prices are much cheaper than in supermarkets. Because of this, the development of traditional markets really needs to be improved, so that public interest increases, changes to traditional markets are needed. The development of traditional markets in Blitar can be seen, among other things, by physical renovations, activities to clean the environment around the market, arrangement of places and grouping of types of merchandise, orderly administration, order and security. Supporting factors include traditional market traders who always follow the advice and directions of market managers, the presence of cleaning staff, and good support from the Trade Department. However, there are also factors that hinder the development of traditional markets in increasing public interest, including: lack of public awareness about not throwing away rubbish, packaging of goods for sale that does not attract public interest, water drains that are often clogged with rubbish. The approach we take is a qualitative approach, such as going directly to traditional markets to see firsthand a clear picture and accurate facts.